ANALYZING TYPES AND LEVELS OF STUDENTS’ ENGLISH-SPEAKING ANXIETY - Setik Nur Hayati; Nita Kaniadewi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2022)
This research was aimed to analyze and describe the types and levels of students' English-speaking anxiety in foreign language learning activities to get broadened understanding of this phenomenon. This study was categorized as descriptive quantitative research. It was conducted at the English Education Department of Muhammadiyah University of Prof. Dr. HAMKA. The participants were the second-semester Students of the Transactional Listening and speaking class. The questionnaires that were given to the participants consisted of 33 statements and were based on FLCAS and adapted from Horwitz and Cope (1986) to find out the dominant types and levels. The author found that the dominant levels of speaking anxiety experienced by the participants were at the